Evaluation of Radiomorphometric Indices of Panoramic Images of Mandible to Estimate Gender and Approximate Age - Seyed Hosein Razavi; Ali Drafshi; Fatemeh Ezoddini; Khalil Sarikhani; Mohammad Khodabakhsh (Journal of Mashhad Dental School)
Background: The evaluation of radiomorphometric indices of the mandible can aid dentists not only in forensic investigations but also in diagnosing developmental abnormalities, age-related changes, and gender-specific characteristics that are crucial for treatment planning. This study aimed to evaluate radiomorphometric indices of mandibular bone on panoramic radiographs for estimating gender and approximate age.Methods and Materials: In this descriptive-cross-sectional study a total 180 panoramic radiographs were retrieved from the Oral and Maxillofacial Radiology Department of Yazd Dental School. Seven different indices were measured: upper ramus breadth (URB), lower ramus breadth (LRB), Condylar ramus height (CH), Projective ramus height (PRH), Coronoid ramus height (CRH), the Gonial angle (GA) and Antegonial notch (AN). Linear and angular measurements were performed on the images. Data analysis was conducted using SPSS 17 with ANOVA, t-tests, linear regression, and logistic regression.Results: The panoramic radiographs were taken from 90 male and 90 female patients with a mean age 39.29 ±15.9 years. For age estimation in males, the most important indices were the AN, GA, PRH, and CRH. In females, the CRH and LRB were the most relevant indices. For gender determination, the AN, PRH, CRH, and CH indices can be used in descending order of significance. Using the prediction equation, gender determination accuracy was 77% for males, 86% for females, and 82% overall. Mean values for all parameters were higher in males than females.Conclusion: Morphometric analysis of mandibular ramus indices on panoramic radiographs is a reliable method for gender determination and age estimation in the Iranian population. These findings support the use of mandibular ramus indices in forensic dentistry for population-specific applications.